C3H8-SCR catalyst and preparation method and application thereof

By using Cu-LTA silica-alumina molecular sieve catalyst for catalytic denitrification under low-oxygen conditions, the problems of low low-temperature efficiency and decreased high-temperature selectivity of C3H8-SCR technology have been solved, achieving efficient and environmentally friendly low-temperature flue gas denitrification.

CN121423019APending Publication Date: 2026-01-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411028802.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

The existing C3H8-SCR technology has low denitrification efficiency at low temperatures, and the N2 selectivity decreases at high reaction temperatures. In addition, the amount of reducing agent C3H8 is too large, resulting in a large number of by-products.

Method used

Using Cu-LTA silica-alumina molecular sieve catalysts, by controlling the pore size to 0.40-0.42 nm, the Si/Al atomic ratio to 15-25, and the Cu content to 1-7%, combined with the catalytic denitrification reaction under low oxygen conditions, intermediate products (CH3NO2 and C2H5NO2) are formed, reducing side reactions and widening the denitrification temperature window.

Benefits of technology

It achieves high efficiency and selectivity in denitrification under low temperature conditions, reduces by-products, avoids the use of ammonia, and reduces the risk of equipment corrosion and secondary pollution. It is suitable for low temperature flue gas denitrification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121423019A_ABST
    Figure CN121423019A_ABST
Patent Text Reader

Abstract

The invention discloses a C3H8-SCR (selective catalytic reduction) catalyst as well as a preparation method and application thereof. The C3H8-SCR catalyst is a Cu-LTA silicon aluminum molecular sieve. The preparation method of the C3H8-SCR catalyst comprises the following steps: adding an acidity regulator into a copper salt solution until the copper salt solution is weak acid, then immersing an LTA silicon-aluminum molecular sieve, drying, and roasting under inert shielding gas to obtain the C3H8-SCR catalyst. The C3H8-SCR catalyst provided by the invention can be used for inhibiting propane from being directly oxidized by oxygen in a catalytic denitration reaction, reducing by-products, widening a temperature window of the denitration reaction, and ensuring higher denitration conversion rate and selectivity when the reaction is carried out at a wider reaction temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of denitrification catalysts, specifically relating to a C3H8-SCR catalyst, its preparation method, and its application. Background Technology

[0002] Nitrogen oxides (NO) x Of which approximately 95% is NO, the sources are quite diverse, with human production and daily life contributing the majority of NO. x Emissions are a major contributor to environmental pollution (acid rain, ozone depletion, photochemical smog, etc.). Currently, ammonia selective catalytic reduction (NH3-SCR) is a relatively mature denitrification technology used in stationary sources such as industrial furnaces and kilns. However, using ammonia as a reducing agent requires a high ammonia-to-nitrogen ratio, leading to high NH3 consumption. Furthermore, ammonia is corrosive, easily causing secondary pollution during storage and transportation, and corroding pipelines in the reactor. The reaction of ammonia with NO produces ammonium nitrate deposits, resulting in severe scaling and high equipment and operating costs. This process uses V2O5-TiO2 series catalysts; V2O5 is a toxic substance with certain impacts on human health and the environment. Since the flue gas composition contains not only NOx but also some unburned organic matter and CO, hydrocarbon selective catalytic reduction of NOx has become a new research hotspot. As an alternative to NH3-SCR, propane-based SCR denitrification technology (C3H8-SCR) solves the various problems associated with using ammonia.

[0003] However, the current C3H8-SCR technology has drawbacks such as low denitrification efficiency at low temperatures (300-400℃), decreased N2 selectivity when the reaction temperature is above 400℃, and excessive input of the reducing agent C3H8 (ACS Catal., 2017, 7, 3501-3509; Appl. Catal. B Environ., 2005, 60, 201-210). Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a C3H8-SCR catalyst, its preparation method, and its applications. The C3H8-SCR catalyst provided by this invention can inhibit the direct oxidation of propane by oxygen in catalytic denitrification reactions, reduce byproducts, and broaden the temperature window of the denitrification reaction. It can maintain high denitrification conversion and selectivity even when the reaction is carried out over a wider range of reaction temperatures.

[0005] The first aspect of the present invention provides a C3H8-SCR catalyst, wherein the catalyst is a Cu-LTA silica-alumina molecular sieve.

[0006] Furthermore, in the catalyst, the pore size of the LTA silica-alumina molecular sieve is 0.40-0.42 nm.

[0007] Furthermore, in the catalyst, the Si / Al atomic ratio of the LTA silica-alumina molecular sieve is 15-25.

[0008] Furthermore, in the catalyst, based on the mass of the catalyst, the mass content of Cu as elemental metal is 1%-7%, preferably 2%-6%.

[0009] Furthermore, in the catalyst, the mass content of LTA silica-alumina molecular sieve is 93%-99%, preferably 94%-98%, based on the mass of the catalyst.

[0010] Furthermore, in the catalyst, the Cu-LTA silica-alumina molecular sieve is a Cu ion-exchanged LTA silica-alumina molecular sieve.

[0011] A second aspect of this invention provides a method for preparing the above-mentioned C3H8-SCR catalyst, comprising the following steps:

[0012] A copper salt solution was added to a weakly acidic environment with an acid regulator, then immersed in LTA silica-alumina molecular sieves, dried, and calcined under an inert protective gas to obtain the C3H8-SCR catalyst.

[0013] Furthermore, the copper salt is at least one of copper chloride, copper nitrate, and copper acetate, and the concentration of the copper salt solution is 2-20 g / L.

[0014] Furthermore, the acidity regulator is at least one of citric acid, oxalic acid, and acetic acid, preferably citric acid; the weak acid is preferably pH 5-6.

[0015] Furthermore, the impregnation conditions are: temperature 30-80℃, time 2-8 hours. After impregnation, the mixture is filtered, washed, and dried, wherein the drying conditions are: 60-100℃, time 6-10 hours.

[0016] Furthermore, the calcination conditions are: a temperature of 530-580℃, a time of 4-8 hours, and an inert protective gas selected from at least one of N2, Ar, and He, with N2 being preferred.

[0017] Furthermore, the preparation method of the LTA silica-alumina molecular sieve includes the following steps:

[0018] An aluminum source, a silicon source, an organic template agent, and an auxiliary template agent are mixed and reacted to obtain a sol. Hydrofluoric acid is then added, and the resulting solid phase is separated and dynamically crystallized to obtain the reaction material. The material is then washed, dried, and calcined to obtain an H-type LTA molecular sieve, which is then subjected to ion exchange to obtain the molecular sieve.

[0019] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the aluminum source is selected from at least one of Al(OH)3, aluminum powder, aluminic acid, aluminum sol and alumina, preferably aluminic acid.

[0020] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the silicon source is selected from at least one of tetraethoxysilane (TEOS), fumed silica and precipitated silica, preferably tetraethoxysilane (TEOS).

[0021] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the organic template agent is 1,2-dimethyl-3-(4-tolyl)imidazolium (12DM3(4MB)IOH).

[0022] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the auxiliary template agent is selected from at least one of tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), and tetrapropylammonium hydroxide (TPAOH), preferably tetramethylammonium hydroxide (TMAOH).

[0023] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the molar ratio of the silicon source (calculated as Si), aluminum source (calculated as Al), organic template agent, auxiliary template agent and hydrofluoric acid is 1:(0.045-0.05):(0.45-0.55):(0.4-0.6):(0.4-0.6).

[0024] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the reaction temperature is 60-80℃ and the time is 4-8h.

[0025] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the crystallization reaction conditions are: temperature of 150-200℃ and time of 48-72h. The stirring speed for dynamic crystallization is 50-300r / min.

[0026] Furthermore, after the crystallization is completed, the product is taken out, mixed with water, and left to stand for 2-6 hours.

[0027] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the drying conditions are: temperature of 80-120℃ and time of 12-24h.

[0028] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the calcination conditions are: temperature of 500-600℃ and time of 4-8h.

[0029] Furthermore, in the preparation method of LTA silica-alumina molecular sieve, the ion exchange step specifically includes: the ion exchange treatment can adopt conventional methods in the prior art. Specifically, in this invention, the H-type LTA molecular sieve is placed in an ammonium salt solution with a concentration of 0.5-3 mol / L, wherein the liquid-to-solid ratio is 50-150 mL / g, and stirred continuously in a water bath at 60-100℃ for 2-6 hours. The above process can be repeated multiple times, preferably 2-5 times; then washing and drying are performed, wherein the drying temperature is 60-100℃ and the time is 6-24 hours. The ammonium salt solution is selected from one or more of ammonium chloride solution or ammonium nitrate solution.

[0030] The third aspect of the present invention provides the application of the above-mentioned catalyst in catalytic denitrification reactions.

[0031] Furthermore, the reaction is a catalytic denitrification reaction carried out under low-oxygen conditions in the presence of NO, C3H8 reducing agent and the above-mentioned catalyst.

[0032] Furthermore, the low-oxygen condition refers to an oxygen volume concentration of less than 5%, preferably 0.5%-3%.

[0033] In the application of this invention, the temperature conditions for the low-temperature catalytic denitrification reaction are: 300-580℃, preferably 300-500℃, and more preferably 300-400℃.

[0034] In this invention, the operating conditions for the reaction are: NO concentration of 700-900 mg / m³. 3 The feed gas molar ratio C3H8:NO = 1:1-3:1, and the reaction volume hourly space velocity is 60,000-100,000 h⁻¹. -1 .

[0035] In the application of this invention, the NO conversion rate is over 90%; the N2 selectivity is 95-100%.

[0036] The catalyst provided by this invention comprises an LTA silica-alumina molecular sieve with an LTA structure. This molecular sieve is combined with the active component Cu, facilitating the entry of C3H8 molecules into the LTA cage of the catalyst, and in the presence of Cu... 2+ and [Cu(OH)] + This invention reduces side reactions by forming intermediate products (CH3NO2 and C2H5NO2) at the catalytic active site. Even at low temperatures, it can efficiently convert NO and C3H8 into N2, CO2, and H2O, exhibiting high NO conversion efficiency and N2 selectivity. When used in denitrification reactions, this catalyst eliminates the need for ammonia addition, yielding clean and environmentally friendly products without secondary pollution. It boasts advantages such as simple process and good economic efficiency, making it a relatively ideal and environmentally friendly denitrification technology, particularly suitable for denitrification of low-temperature flue gas generated by automotive engines, etc.

[0037] In the preparation method of the present invention, NH4 having an LTA structure + Compared to H-LTA aluminosilicate molecular sieves, NH4... + NH4 in type LTA silica-alumina molecular sieves + Cu ions are more easily exchanged by copper ions, thus increasing the exchange capacity of copper ions. 2+ In a weakly acidic environment, Cu 2+ Ions are better exchanged into the molecular sieve, which in turn facilitates Cu exchange. 2+ The ions provide -OH to create more Z[CuOH] sites with propane SCR activity, thereby enhancing the C3H8-SCR activity of the catalyst. Attached Figure Description

[0038] Figure 1 The image shows the XRD pattern of the LTA molecular sieve obtained in Example 1. Detailed Implementation

[0039] The technical solution of the present invention will be further illustrated below through embodiments. These embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0040] In this invention, the X-ray diffraction (XRD) characterization of the molecular sieve samples was performed using an X′Pert PRO type X-ray diffractometer with a Cu target, Kα rays (λ=0.154 18nm), a working current and voltage of 40mA and 40kV, 2θ of 5~60°, and a scanning time of 4min.

[0041] Example 1

[0042] (1)NH4 + Preparation of LTA silica-alumina molecular sieves:

[0043] Al(OH)3·H2O was dissolved in an aqueous solution of 12DM3(4MB)IOH and stirred continuously (500 r / min) until fully dissolved. Then, TMAOH was added, and stirring continued (500 r / min) for 1 h. TEOS was added to the mixture, and stirring (500 r / min) for 3 h was performed to ensure complete hydrolysis of the TEOS. The mixture was then heated to 70 °C and reacted with continuous stirring (500 r / min) for 6 h to obtain a sol. Hydrofluoric acid (HF) was added to the sol, and the mixture was stirred until homogeneous to obtain a solid product. This solid product was transferred to a hydrothermal reactor, sealed, and placed in an oven at 175 °C for crystallization under continuous rotation (170 r / min) for 72 h. The molar ratio of the above substances was TEOS:Al(OH)3·H2O:12DM3(4MB)IOH:TMAOH:HF = 1:0.045:0.5:0.5:0.5.

[0044] The crystallized product was removed and placed in a 500 mL beaker. 300 mL of deionized water was added, and the mixture was stirred until homogeneous and allowed to stand for 4 hours. Subsequently, it was filtered, washed with a large amount of deionized water and ethanol, and the solid product was collected and dried at 100 °C for 24 hours under ventilation to obtain LTA silica-alumina molecular sieve containing OSDA.

[0045] The LTA silica-alumina molecular sieve was placed in a muffle furnace and calcined at 550℃ for 5 hours to obtain H-LTA silica-alumina molecular sieve.

[0046] Weigh 30g of H-LTA silica-alumina molecular sieve into a 1000mL flask, add 800mL of 1mol L... -1 An aqueous solution of NH4NO3 was prepared and heated to 80°C with continuous stirring (500 rpm) for 4 hours. The mixture was filtered, washed with 1 L of deionized water, and the solid product was collected and dried overnight in an oven at 80°C. This process was repeated twice, and after complete drying, NH4NO3 was obtained. + The XRD pattern of the LTA silica-alumina molecular sieve is shown in the figure. Figure 1 The figure shows the characteristic diffraction peaks of LTA aluminosilicate molecular sieves. The pore size of LTA aluminosilicate molecular sieves is 0.40-0.42 nm, and the Si / Al atomic ratio of LTA aluminosilicate molecular sieves is 22:1.

[0047] (2) Preparation of Cu-based LTA silica-alumina molecular sieve catalyst:

[0048] Prepare a solution by mixing 3.4g of copper nitrate with 1L of water, stirring constantly, and then adding 6g of citric acid to adjust the pH to 5, resulting in a pale blue solution. Heat 500mL of the resulting pale blue solution to 80℃, then add 30g of NH4+. +The LTA silica-alumina molecular sieve was added to the mixed solution for impregnation. After impregnation for 4 hours, it was filtered and washed 25 times with deionized water. The resulting solid was then placed in an oven at 80°C and dried for 8 hours. The solid obtained above was ground into powder and calcined under N2 at a temperature of 550°C for 5 hours. After calcination, catalyst powder was obtained. The catalyst powder was pressed into sheets, ground, and sieved to obtain 40-60 mesh particles, thus obtaining the denitrification catalyst.

[0049] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 3%.

[0050] Example 2

[0051] (1)NH4 + The preparation of LTA silica-alumina molecular sieves is the same as in Example 1.

[0052] (2) Preparation of Cu-based LTA silica-alumina molecular sieve catalyst:

[0053] Prepare a solution by mixing 2.3g of copper acetate with 1L of water, and while stirring, add 6g of citric acid to adjust the pH to 5, resulting in a pale blue solution. Heat 500mL of the resulting pale blue solution to 80℃, then add 30g of NH4+. + The LTA silica-alumina molecular sieve was added to the mixed solution for impregnation. After impregnation for 4 hours, it was filtered and washed 25 times with deionized water. The resulting solid was then placed in an oven at 80°C and dried for 6 hours. The solid obtained above was ground into powder and calcined under N2 at a temperature of 550°C for 5 hours. After calcination, catalyst powder was obtained. The catalyst powder was pressed into sheets, ground, and sieved to obtain 40-60 mesh particles, thus obtaining the denitrification catalyst.

[0054] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 2.5%.

[0055] Example 3

[0056] (1)NH4 + The preparation of LTA silica-alumina molecular sieves is the same as in Example 1.

[0057] (2) Preparation of Cu-based LTA silica-alumina molecular sieve catalyst:

[0058] Prepare a solution by mixing 5.6g of copper nitrate with 1L of water, stirring constantly, and then adding 6g of citric acid to adjust the pH to 5, resulting in a pale blue solution. Heat 500mL of the resulting pale blue solution to 80℃, then add 30g of NH4+. +The LTA silica-alumina molecular sieve was added to the mixture for impregnation. After impregnation for 4 hours, it was filtered and washed 25 times with deionized water. The resulting solid was then placed in an oven at 80°C and dried for 6 hours. The solid obtained above was ground into powder and calcined under N2 at a temperature of 550°C for 5 hours. After calcination, the catalyst powder was obtained. (5) The catalyst powder was pressed into sheets, ground and sieved to obtain 40-60 mesh particles to prepare the denitrification catalyst.

[0059] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 5%.

[0060] Example 4

[0061] (1)NH4 + Preparation of LTA silica-alumina molecular sieves:

[0062] Except for changing the crystallization time to 60h, the rest of the preparation method is the same as in Example 1.

[0063] (2) Preparation of Cu-based LTA silica-alumina molecular sieve catalyst:

[0064] Prepare a solution by mixing 3.4g of copper nitrate with 1L of water, stirring constantly, and then adding 6g of citric acid to adjust the pH to 5, resulting in a pale blue solution. Heat 500mL of the resulting pale blue solution to 80℃, then add 30g of NH4+. + The LTA silica-alumina molecular sieve was added to the mixed solution for impregnation. After impregnation for 4 hours, it was filtered and washed 25 times with deionized water. The resulting solid was then placed in an oven at 80°C and dried for 6 hours. The solid obtained above was ground into powder and calcined under N2 at a temperature of 550°C for 5 hours. After calcination, catalyst powder was obtained. The catalyst powder was pressed into sheets, ground, and sieved to obtain 40-60 mesh particles, thus obtaining the denitrification catalyst.

[0065] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 3%.

[0066] Example 5

[0067] (1)NH4 + Preparation of LTA silica-alumina molecular sieve: The molar ratio of TEOS:Al(OH)3·H2O:12DM3(4MB)IOH:TMAOH:HF was changed to 1:0.05:0.5:0.5:0.5, and the rest of the preparation method was the same as in Example 1.

[0068] (2) Preparation of Cu-based LTA silica-alumina molecular sieve catalyst:

[0069] Prepare a solution by mixing 3.4g of copper nitrate with 1L of water, add 6g of citric acid while stirring, and adjust the pH to 5 to obtain a light blue solution; heat 500mL of the solution from step (2) to 80℃, and then add 30g of NH4+. + The LTA silica-alumina molecular sieve was added to the mixture for impregnation. After impregnation for 4 hours, it was filtered and washed 25 times with deionized water. The resulting solid was then placed in an oven at 80°C and dried for 6 hours. The solid obtained in step (3) was ground into powder and calcined under N2 at a temperature of 550°C for 5 hours. After calcination, the catalyst powder was obtained. The catalyst powder was pressed into sheets, ground and sieved to obtain 40-60 mesh particles, thus obtaining the denitrification catalyst.

[0070] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 3%.

[0071] Comparative Example 1

[0072] Catalyst preparation:

[0073] Prepare a solution by mixing 5.6g of copper nitrate with 1L of water, adding 6g of citric acid while stirring to adjust the pH to 5, resulting in a light blue solution. Heat 500mL of the light blue solution to 80℃, then add 30g of ZSM-5 molecular sieve to the mixture for impregnation. After impregnation for 4 hours, filter the solution, wash it 25 times with deionized water, and then dry the resulting solid in an oven at 80℃ for 6 hours. Grind the solid into powder and calcine it under N2 at 550℃ for 5 hours to obtain catalyst powder. Press the catalyst powder into sheets, grind and sieve it to obtain 40-60 mesh particles, thus obtaining the denitrification catalyst.

[0074] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 5%.

[0075] Comparative Example 2

[0076] Catalyst preparation:

[0077] Prepare a solution by mixing 3.4 g of copper nitrate with 1 L of water to obtain a pale blue solution; heat 500 mL of the obtained pale blue solution to 80 °C, then add 30 g of NH4+. + The LTA molecular sieve was added to the mixture for impregnation. After impregnation for 4 hours, it was filtered and washed 25 times with deionized water. The resulting solid was then placed in an oven at 80°C and dried for 6 hours. The solid obtained above was ground into powder and calcined under N2 at a temperature of 550°C for 5 hours. After calcination, catalyst powder was obtained. The catalyst powder was pressed into sheets, ground, and sieved to obtain 40-60 mesh particles, thus obtaining the denitrification catalyst.

[0078] In the catalyst, based on the total mass of the catalyst, the mass content of the active component Cu is 3%.

[0079] Comparative Example 3

[0080] (1) H-type LTA silica-alumina molecular sieve was selected and prepared in the same manner as in Example 1.

[0081] (2) The catalyst preparation is the same as in Example 1, except that H-type LTA silica-alumina molecular sieve is used instead of NH4. + Type LTA molecular sieve.

[0082] Test case

[0083] Activity evaluation experiments were conducted on the above catalysts, and the activity evaluation test methods are as follows:

[0084] To simulate actual flue gas conditions, the NO concentration in the mixed gas mixture was 800 mg / m³. 3 The oxygen volume concentration was 3%, the C3H8:NO molar ratio was 1:1, the catalyst mass was 0.1 g, the total gas flow rate was 180 mL / min, and the space velocity was 80,000 h⁻¹. -1 The reactor was a continuous flow fixed-bed reactor with a programmed heating rate of 10℃ / min, sequentially increasing to 300, 350, 400, 450, and 500℃ from room temperature. The temperatures were then held at the set points for 0.5 hours to allow stabilization before product analysis. The NO conversion efficiency of different catalysts and the N2 selectivity of the reaction were calculated and evaluated. The calculation formulas are as follows:

[0085]

[0086] Table 1 shows the test results of the catalysts obtained in each example.

[0087]

Claims

1. A C 3 H 8 -SCR catalyst, wherein the catalyst is a Cu-LTA silico-alumina molecular sieve.

2. The catalyst according to claim 1, characterized in that, The pore size of the LTA silico-alumina molecular sieve is 0.40-0.42 nm. And / or, the Si / Al atomic ratio of the LTA silico-alumina molecular sieve is 15-25.

3. The catalyst of claim 1, wherein The mass content of Cu in the form of metal elementary substance is 1-7% based on the mass of the catalyst; and / or, the mass content of the LTA silico-alumina molecular sieve is 93-99% based on the mass of the catalyst. 4.A method for preparing the C 3 H 8 -SCR catalyst according to any one of claims 1-3, comprising the following steps: adding an acid regulator to the copper salt solution to a weak acid environment, then immersing the LTA silico-alumina molecular sieve, drying, and calcining under an inert protective gas to obtain the C 3 H 8 -SCR catalyst.

5. The preparation method according to claim 4, characterized in that, The copper salt is at least one of copper chloride, copper nitrate and copper acetate, and the concentration of the copper salt solution is 2-20 g / L. And / or, the acid regulator is at least one of citric acid, oxalic acid and acetic acid, preferably citric acid; and the pH value of the weak acid environment is 5-6.

6. The preparation method according to claim 4, characterized in that, The impregnation conditions are: temperature 30-80℃, time 2-8 hours; after impregnation, suction filtration, washing and drying, wherein the drying conditions are: temperature 60-100℃, time 6-10 hours. And / or, the calcination conditions are: temperature 530-580℃, time 4-8 hours, and the inert protective gas is at least one of N 2, Ar and He.

7. The preparation method according to claim 4, characterized in that, The method for preparing the LTA silico-alumina molecular sieve comprises the following steps: mixing an aluminum source, a silicon source, an organic template agent and an auxiliary template agent to obtain a sol, then adding hydrofluoric acid, separating the obtained solid phase, and performing dynamic crystallization to obtain a reaction material, which is washed, dried and calcined to obtain an H-type LTA molecular sieve, and then ion exchange is performed to obtain the molecular sieve.

8. The preparation method according to claim 7, characterized in that, The aluminum source is at least one of Al(OH) 3, aluminum powder, meta-aluminate, aluminum sol and aluminum oxide; the silicon source is at least one of tetraethoxysilane (TEOS), fumed silica and white carbon black; the organic template agent is 1,2-dimethyl-3-(4-methylphenyl)imidazole; and the auxiliary template agent is at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide. And / or, the molar ratio of the amounts of the silicon source (calculated as Si), the aluminum source (calculated as Al), the organic template agent, the auxiliary template agent and hydrofluoric acid is 1:(0.045-0.05):(0.45-0.55):(0.4-0.6):(0.4-0.6).

9. The preparation method according to claim 7, characterized in that, The reaction temperature is 60-80℃, and the reaction time is 4-8h. And / or, the crystallization reaction conditions are: temperature 150-200℃, time 48-72h; and the stirring speed of the dynamic crystallization is 50-300r / min.

10. The preparation method according to claim 7, characterized in that, The drying conditions are: temperature 80-120℃, time 12-24h. And / or, the calcination conditions are: temperature 500-600℃, time 4-8h.

11. Use of the catalyst of any one of claims 1-3 or the catalyst prepared by the method of any one of claims 4-10 for catalyzing a denitration reaction.

12. Use according to claim 11, characterized in that, The reaction is a catalytic denitration reaction in the presence of NO, C3H8 reducing agent and the catalyst under low oxygen conditions.

13. Use according to claim 11 or 12, characterised in that, The low oxygen conditions refer to a volume concentration of oxygen less than 5%.

14. Use according to claim 11 or 12, characterised in that, The temperature condition of the low-temperature catalytic denitration reaction is 300-580°C, preferably 300-500°C. and / or the operating conditions of the reaction are: concentration of NO 700-900 mg / m 3 feed gas molar ratio C3H8:NO = 1:1-3:1, reaction volume space velocity 60000-100000 h -1 .